Reimagining Healthcare Service Quality: A SERVQUAL-Based Analysis of Patient Satisfaction - Mirnawati Mirnawati; Sitti Rahmah; Virna Museliza; Tran Thai Ha Nguyen; Muhammad Firmansyah (International Journal of Information System and Innovation Management (IJISIM), 2026)
Delivering patient-centered healthcare services requires continuous innovation in service quality management, particularly in primary healthcare institutions facing increasing service demand and resource constraints. This study aims to reimagine healthcare service quality by examining how the five SERVQUAL dimensions contribute to patient satisfaction at the Tembilahan City Community Health Center, Indragiri Hilir Regency. A qualitative field research design was employed using direct observation, semi-structured interviews, and document analysis to capture the perspectives of healthcare providers and patients. The findings reveal that the health center demonstrates satisfactory performance across the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, indicating a generally positive level of patient satisfaction. Nevertheless, several structural and operational challenges remain, including inadequate facilities, high patient volumes, shortages of human resources, and inefficiencies in administrative services, which limit the delivery of fully patient-centered care. The study contributes by providing a SERVQUAL-based qualitative evaluation that identifies priority areas for service innovation in primary healthcare. These findings offer practical insights for healthcare managers and policymakers in designing strategies to strengthen service quality and improve patient satisfaction in community health centers.